2018
DOI: 10.2320/matertrans.m2018141
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Microstructure and Tribological Properties of Plasma, High Velocity Oxy-Fuel and Detonation Sprayed Coatings from an Iron-Based Powder

Abstract: The microstructure and tribological properties of Fe-based amorphous coatings fabricated by plasma spray, high-velocity oxygen-fuel (HVOF) spray and detonation spray have been compared. The relationship between spray technique, amorphous content, porosity and wear resistance behavior was investigated. The microstructures of the coatings were mainly composed of amorphous phase. The amorphous content of the coatings made by various spray techniques were 79.39%, 85.26% and 88.14%, respectively. The coatings exhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Owing to reduced cost in comparison with other metallic glasses, Fe-based metallic glasses are of particular interest for practical applications. Several attempts to deposit Fe-based metallic glass coatings by the thermal spraying methods have been made [12][13][14][15][16][17]. The formation of metallic glass coatings by thermal spraying is a challenge, as, during the deposition, conditions should be created either to preserve an amorphous structure of the material (in the case of spraying of amorphous alloy powders) or to produce amorphous layers through melting of the particles and rapid solidification.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Owing to reduced cost in comparison with other metallic glasses, Fe-based metallic glasses are of particular interest for practical applications. Several attempts to deposit Fe-based metallic glass coatings by the thermal spraying methods have been made [12][13][14][15][16][17]. The formation of metallic glass coatings by thermal spraying is a challenge, as, during the deposition, conditions should be created either to preserve an amorphous structure of the material (in the case of spraying of amorphous alloy powders) or to produce amorphous layers through melting of the particles and rapid solidification.…”
Section: Introductionmentioning
confidence: 99%
“…Despite partial crystallization, the ability of the coatings to resist localized corrosion allowed the authors to recommend them as surface protection for marine environments. Xie et al [15] presented a comparative analysis of the microstructure and mechanical properties of Fe 48 Mo 14 Cr 15 Y 2 C 15 B 6 coatings obtained by detonation, plasma, and high-velocity oxygen fuel spraying. It was found that the detonation coatings possess the highest content of the amorphous phase among the studied coatings.…”
Section: Introductionmentioning
confidence: 99%
“…Variation in particle size influences the corrosion properties of coating material. A decrease in spraying particle size increases the corrosion resistance of coating materials [8]. The best quality of spray can be obtained by optimising HVOF parameters such as particle velocity, powder feed rate, and spray distance, and in the response optimisation, the spray distance is indicated as the most significant factor affecting the spray/coating quality [9].…”
Section: Introductionmentioning
confidence: 99%
“…During the spraying process, oxidation of the sprayed powder should be avoided, as the oxide lms formed on the surface favor heterogeneous nucleation, and negatively affect the properties of the coatings [17][18][19][20][21][22]. Among thermal spraying methods, the impulse nature of detonation spraying allows the formation of wear resistant and dense coatings with low crystalline phase content [23]. The results of the investigation of the tribological and corrosion properties of Fe 51.33 Cr 14.9 Mo 25.67 Y 3.4 C 3.44 B 1.26 detonation coatings with high content of amorphous phase (content of crystalline phase 14.46 wt.%) and studying of wear mechanisms was presented in [24].…”
Section: Introductionmentioning
confidence: 99%